PELAKSANAAN SUPERVISI PENGAJARAN OLEH KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMK NEGERI 1 BANDA ACEH - Siti Wahidah (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2015)
Abstract: Supervision of teaching is a principal effort in coaching teachers in order to improve their quality of teaching. The aim of the study was to identify the teaching supervision programs, teaching supervision implementation, supervision techniques, and inhibiting factors in supervision implementation conducted by principal. This research used descriptive method and qualitative approach. Data collection techniques used were observation, interview, and documentation study. Subjects of the research were principal, vice-principals, senior teachers and head of the program expertise. The results of the research showed that 1) Teaching supervision programs at State Vocational High School (SMKN) 1 Banda Aceh were oriented to the guidance of the task of teachers in order to improve their performance by involving the vice principals, senior teachers and head of the program expertise. During the drafting of the program, the formulation of objectives was poorly supported by the supporting facilities and implementation strategies. 2) There are several stages (cycles) in the implementation of teaching supervision to improve the performance of the teachers. It starts from the initial planning stage, the observation stage, and the final stage (discussion feedback), so that the learning process will be more effective, but not all teachers have been supervised yet in compliance with the program. 3) Techniques used by the principal were individual, group, and clinical supervision technique. 4) Follow-up is done by providing assistance and guidance to teachers who are experiencing difficulties in carry out their duties as a teacher, and improving teacher’s professionalism through teacher conferences and training courses. However, it was not implemented as planned in the supervision program. 5) Inhibiting Factors in the implementation of the teaching supervision is low competence of supervisor appointed, there were unplanned activities outside supervision schedule, and it is hard to change old habits. Keywords: Teaching Supervision and Teachers’ Performance